Plasma catecholamines in the acute phase of the response to myocardial infarction. - Little, R; Frayn, K; Randall, P; Stoner, H; Morton, C; Yates, D; Laing, G (1986)
Plasma catecholamine (adrenaline, noradrenaline and dopamine) concentrations have been measured in 48 patients within 6 hours of the onset of symptoms of an acute myocardial infarction. The concentrations of all three catecholamines were elevated, and there were positive correlations between plasma noradrenaline concentrations and the severity of infarct as assessed by the coronary prognostic index and serum LDH levels. Plasma glucose, free fatty acid, lactate and cortisol levels were elevated while insulin levels were reduced. The site of infarction did not influence the pattern of hormonal and metabolic responses although heart rate was significantly lower in the inferior than in the anterior infarct group. Seven patients went into ventricular fibrillation shortly (less than 1.8 h) after blood sampling. Plasma catecholamine concentrations were markedly elevated in these patients with levels similar to those previously reported after cardiac arrest.